2020
DOI: 10.1002/jmv.25889
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COPD and smoking history on the severity of COVID‐19: A systemic review and meta‐analysis

Abstract: Comorbidities are associated with the severity of coronavirus disease 2019 . This meta-analysis aimed to explore the risk of severe COVID-19 in patients with pre-existing chronic obstructive pulmonary disease (COPD) and ongoing smoking history. A comprehensive systematic literature search was carried out to find studies published from December 2019 to 22 March 2020 from five databases. The languages of literature included English and Chinese. The point prevalence of severe COVID-19 in patients with pre-existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

38
620
10
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 671 publications
(707 citation statements)
references
References 18 publications
(37 reference statements)
38
620
10
39
Order By: Relevance
“…Our analysis also points out to reduced importance of respiratory diseases and smoking. Both conditions appear as factors in most at-risk definitions [3,5]: Chronic obstructive pulmonary disease has been associated with severe COVID-19 in multiple (though not all [6]) studies [20], while the role of smoking has been somewhat controversial [20,21]. The discrepancies between our analysis and previous reports likely stem from the different cohorts analyzed: SARS-CoV-2 positive individuals, ranging from asymptomatic to severe COVID-19 versus hospitalized COVID-19 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis also points out to reduced importance of respiratory diseases and smoking. Both conditions appear as factors in most at-risk definitions [3,5]: Chronic obstructive pulmonary disease has been associated with severe COVID-19 in multiple (though not all [6]) studies [20], while the role of smoking has been somewhat controversial [20,21]. The discrepancies between our analysis and previous reports likely stem from the different cohorts analyzed: SARS-CoV-2 positive individuals, ranging from asymptomatic to severe COVID-19 versus hospitalized COVID-19 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24][25][26] Only one 17 of the studies reported unadjusted and adjusted ORs using multivariate analysis; after adjusting for confounding by age, maximum temperature at admission, respiratory failure, severe illness, albumin, creatinine, procalcitonin, and C-reactive protein level, the effect of smoking on disease severity increased (unadjusted: OR 12.19, 95% CI 1.76-84.31, p = .011; adjusted: OR 14.29, 95% CI 1.58-25.0, p = .018). Three peer-reviewed meta-analysis papers 6,34,35 on association between smoking and COVID-19 were also based on unadjusted ORs, but with fewer studies included.…”
Section: Limitationsmentioning
confidence: 99%
“…There is an ongoing debate on whether smoking is a risk factor for COVID-19 severity. Although some regard it as a risk factor 9,27 , others found no significant alliance between smoking and the . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%